(untitled) (Bangladesh Journal of Botany, 2021)
The present study was hypothesized to evaluate a set of SSRs for the assessment of genetic variations in Asparagus officinalis L. and their allied species. Nine genic SSR markers were especially developed for Asparagus genome and employed for DNA profiling studies of Asparagus species. These SSRs markers have revealed the allelic polymorphism ranging from 1.0 to 2.0. Allele frequency was found highest for psbD-trnL (1.0), petB (1.0) and AG7 (1.0), while it was lowest for ZHD1 (0.1). Polymorphism Information content (PIC) was highest for TC7 (0.9) while it was lowest (0.0) for psbD-trnL, petB and AG7 respectively. The genetic similarity coefficients were found to range from 0.42 to 1.0. The UPGMA clustering algorithm based on SSRs data have clustered Asparagus species into 4 groups (I, II, III & IV) indicating Asparagus officinalis (L.) cultivars and allied species in the first clade, while Asparagus officinalis (L.) ‘Gersengum’, Asparagus densiflorus (Kunth) Jessop, and Asparagus racemosus willd. were clustered in separate clades respectively. The present study has endorsed the origin status of Asparagus officinalis and their allied species. A. officinalis cultivars and other allied Asparagus species are clustered in separate clades, and it was revealed that they have monophyletic origin. It was established that SSRs markers could be informative markers for the differentiation of Asparagus officinalis cultivars, and their allied Asparagus species. Bangladesh J. Bot. 50(3): 595-602, 2021 (September)